Legal Protection Mechanishm for Victims of Traficking in Persons (TPPO) in Sukabumi City - Widia Putri; Ujuh Juhana; R. Eriska Ginalita Dwi Putri; Xie Guilin; Deng Jiao; Yuanyuan Wang (Rechtsnormen: Journal of Law, 2023)
Background.  Human trafficking is a contemporary version of slavery, ensuring the rights of victims to feel safe is crucial to create an efficient judicial process. Purpose. This research aims to identify the mechanisms of legal protection for TPPO victims in Sukabumi City and the supporting and inhibiting factors that influence them. The research methodology used is normative law with data sources including interviews, observations, and literature studies. Method. The data is processed using qualitative analysis, conducted at the Regional Technical Service Unit for Women and Children Protection. Results. The mechanisms of legal protection provided include the complaint process, victim outreach, case management, temporary shelter, and mediation. The supporting factors include collaboration among legal institutions. Conclusion. The inhibiting factors include limited budget and lack of Safe Houses (Shelters) or Trauma Centers.